2012
DOI: 10.1094/ats-2012-1220-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Golf Course Environmental Profile Measures Pesticide Use Practices and Trends

Abstract: To develop a national golf course environmental profile, a survey was sent to 16,194 superintendents at US golf facilities to determine pesticide storage and mixing and loading practices; use of written pesticide emergency plans, integrated pest management plans, and pesticide application plans; restrictions to pesticide operations; number of certified pesticide applicators; pest management tactics; trends in pesticide use; and pesticide use. The response rate was 20.5%. Analysis of data indicated responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Part of a larger effort known as the GCSAA Golf Course Environmental Profile, this survey was one of five national surveys conducted between 2006 and 2009 with the objective of developing a comprehensive environmental profile of golf courses in the United States (Lyman et. al., 2007; Throssell et.al., 2009a, 2009b; Lyman et al, 2012a, 2012b). In 2016, a follow‐up survey was conducted through the Environmental Institute for Golf (Lawrence, KS) and was funded by the United States Golf Association (USGA, Far Hills, NJ).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Part of a larger effort known as the GCSAA Golf Course Environmental Profile, this survey was one of five national surveys conducted between 2006 and 2009 with the objective of developing a comprehensive environmental profile of golf courses in the United States (Lyman et. al., 2007; Throssell et.al., 2009a, 2009b; Lyman et al, 2012a, 2012b). In 2016, a follow‐up survey was conducted through the Environmental Institute for Golf (Lawrence, KS) and was funded by the United States Golf Association (USGA, Far Hills, NJ).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Thus, management intensity of golf course turf often exceeds athletic fields, sod production fields, as well as residential and commercial lawns. A survey of golf course superintendents reported that herbicide use on golf courses increased 10 to 25% in 2007 compared to an average year (Lyman et al 2012). …”
Section: Other Reports Of Resistancementioning
confidence: 99%
“…W ater use and conservation practices on U.S. golf courses were documented for the first time in a 2006 survey conducted by the Golf Course Superintendents Association of America (GCSAA) (Throssell et al, 2009a). Part of a larger effort known as the “GCSAA Golf Course Environmental Profile,” the water use survey was one of five national surveys conducted between 2006 and 2009, with the objective of developing a comprehensive environmental profile of golf courses in the United States (Lyman et al, 2007, 2012a, 2012b; Throssell et al, 2009a, 2009b). In the fall of 2014, the second phase of the Golf Course Environmental Profile, conducted by the GCSAA and funded by the Environmental Institute for Golf through sponsorship by the U.S.…”
Section: Introductionmentioning
confidence: 99%